DIABETES MELLITUS, DIABETIC NEPHROPATHY, CHILDREN: CERTAINISSUES - Fomina, A. P. (Ukrainian Journal of Nephrology and Dialysis, 2017)
The report presented the current approach to diabetes and chronic kidney disease relationship, the problem of nutritional carbohydrates and their role in the diabetes epidemiological situation. The relevant diagnostic and genetic tests in diabetic nephropathy, particularly in children, were outlined. Evidence based treatment was considered according to renal function and pediatric specification.